The Zeta Potential Measurements in Sandpacks Saturated with Monovalent Electrolytes - Duy Thanh, Luong (VNU Journal of Science: Mathematics - Physics; Vol 34 No 2DO - 10.25073/2588-1124/vnumap.4238, 2018)
Measurements of the zeta potential in sandpacks saturated with monovalent electrolytes at six different electrolyte concentrations have been reported. The values we record are classified into two groups based on the magnitude of the zeta potential: group 1 (samples S1 and S2) and group 2 (samples S3 and S4). The measured zeta potential in magnitude in group 1 is much smaller than that in group 2 and in literature at the same electrolyte concentration. The reason for a big variation of the zeta potential between group 1 and group 2 may be due to the difference in technique of making sand particles of different size leading to change of particle surface properties. Consequently, the zeta potential that depends on the surface properties would vary. The results show that there is a gradual decrease in the zeta potential with increase in monovalent electrolyte concentration (from 10−4 M to 10−2 M). Additionally, the empirical expressions between the zeta potential and electrolyte concentration are obtained in this work for both group 1 and group 2. The obtained expression for group 2 is in good agreement with those available in literature. From the experimental data in combination with a theoretical model, the binding constants for Na+ and K+ cations are obtained for the samples of group 2 and they are in the same range reported in literature for silica-based samples. Keywords Streaming potential, zeta potential, porous media, sands, electrolytes References   [1] B. Wurmstich, F. D. Morgan, Geophysics 59 (1994) 46–56. [2] R. F. Corwin, D. B. Hoovert, Geophysics 44 (1979) 226–245. [3] F. D. Morgan, E. R. Williams, T. R. Madden, Journal of Geophysical Research 94 (1989) 12.449–12.461. [4] H. Mizutani, T. Ishido, T. Yokokura, S. Ohnishi, Geophys. Res. Lett. 3 (1976). [5] M. Trique, P. Richon, F. Perrier, J. P. Avouac, J. C. Sabroux, Nature (1999) 137–141. [6] A. A. Ogilvy, M. A. Ayed, V. A. Bogoslovsky, Geophysical Prospecting 17 (1969) 36–62. [7] P. W. J. Glover, E. Walker, and M. D. Jackson, Geophysics 77 (2012) D17–D43. [8] S. R. Pride and F. D. Morgan, Geophysics 56 (1991) 914-925. [9] Vinogradov, J., M. Z. Jaafar, and M. D. Jackson, Journal of Geophysical Research Atmospheres 115 (2010) B12204. [10] O. Stern, Z. Elektrochem 30 (1924) 508–516. [11] T. Ishido, H. Mizutani, Journal of Geophysical Research 86 (1981) 1763– 1775. [12] H. M. Jacob, B. Subirm, Electrokinetic and Colloid Transport Phenomena, Wiley-Interscience, 2006. [13] Revil A. and P. W. J. Glover, Physical Review B 55 (1997) 1757-1773. [14] Lide, D.R., 2009, Handbook of chemistry and physics, 90th ed., CRC Press. [15] Luong Duy Thanh, Rudolf Sprik, VNU Journal of Science: Mathematics – Physics, (2017) streaming potential coefficient in unconsolidated samples saturated with monovalent electrolytes (accepted). [16] B. J. Kirby, E. J. Hasselbrink, Electrophoresis 25 (2004) 187–202. [17] Dove, P. M., and J. D. Rimstidt, Reviews in Mineralogy and Geochemistry 29 (1994) 259-308. [18] Kosmulski, M., and D. Dahlsten, Colloids and Surfaces, A: Physicocemical and Engineering Aspects 291 (2006) 212-218.